2012
DOI: 10.1007/s00431-012-1909-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with community-acquired pneumonia in hospitalised children and adolescents aged 6 months to 13 years old

Abstract: These findings contribute favourably to effectively minimising the risk factors related to the disease process and natural history of community-acquired pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
4
17
1
Order By: Relevance
“…13 In this study, we found that housing variables were not independently associated with pneumonia; rather, we found that broader socioeconomic indicators such as higher education status of the mother and a higher family income were protective for coinfection, which is consistent with previous studies showing that such risk factors are associated with childhood pneumonia in resource-limited settings, including Egypt, 14 Brazil, 15 and India. 16 We also demonstrate that for those under 12 months of age, breast-feeding was associated with a lower risk of concurrent pneumonia.…”
Section: Discussionsupporting
confidence: 90%
“…13 In this study, we found that housing variables were not independently associated with pneumonia; rather, we found that broader socioeconomic indicators such as higher education status of the mother and a higher family income were protective for coinfection, which is consistent with previous studies showing that such risk factors are associated with childhood pneumonia in resource-limited settings, including Egypt, 14 Brazil, 15 and India. 16 We also demonstrate that for those under 12 months of age, breast-feeding was associated with a lower risk of concurrent pneumonia.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, this study does not improve the literature already documented on pneumonia. However, some studies have shown that breast feeding has protective effect on pneumonia (Barsam et al, 2013;Chisti et al, 2011;César et al, 1999;Lamberti et al, 2013). This study also shows that "immediate" initiation and "hours" initiation of breast feeding has similar impact on diarrhea amongst infant and children generally; so breast feeding within 24 h is protective as compared to breast feeding >24 h later.…”
Section: Discussionmentioning
confidence: 99%
“…1 Preterm infants face increased risks of pneumonia, retinopathy, necrotizing enterocolitis (NEC), and sepsis. Breast milk provides protection against these complications, 2-7 and for this reason, the American Academy of Pediatrics recommends that all infants, particularly those weighing less than 1500 grams at birth, receive human milk. 8 The robust immunological profile of breast milk may contribute to this protective influence on vulnerable infants.…”
Section: Introductionmentioning
confidence: 99%